The Relationship of Pyroptosis-Related Genes, Patient Outcomes, and Tumor-Infiltrating Cells in Bladder Urothelial Carcinoma (BLCA) - Xie, Ruiyan; Xie, Ming; Zhu, Litong; Chiu, Joanne W. Y.; Lam, Wayne; Yap, Desmond Y. H. (Frontiers in Pharmacology, 2022)
Introduction: The role of pyroptosis and its effect on tumour infiltrating cells (TICs) in the pathogenesis and treatment outcomes of patient with bladder urothelial carcinoma (BLCA) remains unclear. Methods: We conducted a bioinformatic analysis on the pyroptosis-related genes (PRGs) and TICs using data from public domains, and evaluated their impact on pathogenesis and clinical outcomes of BLCA patients. A risk score based on PRGs and a prognostic risk model that incorporated patient demographics, tumour characteristics and differentially expressed genes (DEGs) were developed. Results: Twenty-three DEGs of 52 PRGs were identified in BLCA and normal samples from TCGA database. Missense mutations and single nucleotide polymorphisms in PRGs are the most common genetic abnormalities. Patients with high PRGs risk scores showed inferior survival compared to those with low risk scores. The prognostic risk model based on patient demographics, tumour characteristics and DEGs showed good predictive values for patient survival at 1, 3 and 5 years in BLCA patients. Caspase-8 (CASP8) was the only intersection gene of prognostic genes, DEGs and different genes expressed in tissue. Patients with high CASP8 expression had improved survival, and increased CASP8 expression was observed in activated CD4 memory T cells, follicular T helper cells, resting NK cells, M0 macrophages and activated dendritic cells. CASP8 expression also showed a positive correlation with IL7R expression – a key cell marker of CD4 memory T cells. CASP8 expression also showed correlations with immune checkpoints (PDCD1, CD274 and CTLA4) and response to immune checkpoint inhibitors. Conclusion: Our data suggest that PRGs, especially CASP8, showed strong associations with patient outcomes and TICs in BLCA. If validated, these results could potentially aid prognostication and guide treatment in BLCA patients.